LARGE VOLUME RE-IRRADIATION IS A VIABLE OPTION IN PATIENTS WITH RECURRENT REFRACTORY GLIOBLASTOMA. (3rd October 2018) - Back, Michael; Chan, Joseph; Jayamanne, Dasantha
Abstract: PURPOSE: Current practice in re-irradiation (reRT) of patients with previously treated Glioblastoma (GBM) has generally been limited to small volume reRT often with stereotactic procedures. Less evidence exists for the safety, toxicity and outcomes of patients who undergo large volume reRT. This study investigates outcomes of large volume reRT in patients with recurrent refractory GBM. METHODS: Patients with GBM managed with radiation therapy were entered into a prospective ethics approved database. Patients receiving fractionated reRT from 2009–2017 were identified. Potential prognostic data were analysed for the primary endpoint of overall survival (OS) duration post reRT, such as tumour type, tumour site, age, time from diagnosis, ECOG status, MRC Neurological Scale, PTV volume, and use of bevacizumab (BEV). Kaplan Meier survival was calculated and differences between groups assessed by log-rank and Cox regression analyses. RESULTS: Seventy-two patients were managed with ReRT, including 51 patients with GBM. Median PTV was 117.4cm 3 ; 92% received 35-40Gy in 15 fractions; and 80% patients received concurrent BEV and 88% post-reRT BEV. Only one episode of radiation necrosis occurred, and was in a patient with no concurrent BEV. Median OS post reRT of the 51 patients was 7 months (95% CI: 6.2–7.8). ECOG 0–1 had a median OS of 9 months (95% CI: 8.1–9.9) compared with 6 months for ECOG 2–3 (95% CI: 4.4–7.6; p=0.05). Time from diagnosis (p<0.01) was associated with improved survival but not age (p=0.16); MRCscale(p=0.19); PTV volume (p=0.62) or tumour site (p=0.72). Concurrent or post-reRT BEV was not associated with OS (p=0.57; but noting that 88% received BEV and the median OS was 7 months versus 4 months with no BEV). CONCLUSION: Large volume reRT with BEV produces a meaningful survival in patients with GBM, especially in patients with good performance status. It should be considered as a late salvage therapy in chemorefractory disease.